Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting

Concurrent glycerol oxidation and hydrogen production on Ce-Co oxide/carbon for sustainable biomass valorization - Jana, Jayasmita; Chowdhury, Somnath; Saha, Avishek; Kang, Sung Gu; Hur, Seung Hyun; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Integrating glycerol oxidation with water electrolysis offers a sustainable route for hydrogen production while enabling concurrent generation of industrially relevant C1-C3 value-added materials. This system replaces kinetically sluggish oxygen evolution reaction (OER) simultaneously delivering H-2 at the cathode with high turnover frequency, thereby lowering the overall cell voltage and enabling the valorization of glycerol, a major by-product of the biodiesel industry. However, the development of an efficient bifunctional electrocatalysts capable of driving cathodic as well as anodic half-cell reactions remains a key challenge. Herein, we present a cerium-cobalt oxide composite modified with an amorphous carbon layer (Ce,Co-O/C) as an effective bifunctional catalyst for glycerol-assisted water electrolysis. The interfacial electron distribution across the Co-Ce oxide heterojunction generated abundant redox-active sites and accelerates reaction kinetics, while the conductive carbon layer facilitates rapid charge transfer and imparts improved stability. Consequently, the Ce, Co-O/C catalyst exhibited high formate selectivity at 1.4 V (vs RHE) at room temperature and delivers a low cell voltage of 1.90 V at 100 mA cm(-2) in a symmetric Ce,Co-O/C vertical bar vertical bar Ce,Co-O/C system, maintaining operational stability over 100 h. This work provides a promising interface-engineering for designing self-supported bifunctional electrocatalysts toward integrated biomass assisted co-electrolysis systems.
Keywords: Amorphous carbon; biomass valorization; electrocatalysis; energy conversion; green hydrogen